Case Study Report on Kartagener’s Syndrome - an Inherited Disorder - Uma M,; Rajalakshmi S, (The Bioscan, 2025)
This case presents an 18-year-old male with a complex presentation, including neurological, respiratory, and dermatological symptoms. The patient’s viral encephalitis is likely the underlying cause of the altered sensorium, and herpes zoster in the T2-T3 dermatomes is indicative of a localized reactivation of the varicella-zoster virus, often seen in immunocompromised states or viral infections. The patient’s respiratory distress and pneumonia complicate the picture, likely compounded by aspiration pneumonitis following self-extubation. The combination of these findings warrants a multi-disciplinary approach to management, including antiviral therapy for herpes zoster (acyclovir), antibiotic therapy for pneumonia (ceftriaxone), seizure management (levetiracetam), and symptomatic management for the altered sensorium and aspiration pneumonitis. Additionally, the poor cardiovascular status, along with altered mental status, requires close monitoring and aggressive supportive care.